Pelatihan website Desa Bleber sebagai sarana akuntabilitas dan transparansi publik - Setyorini, Nurul; Sholeh, Khabib; Riyanto, Riko Oktavian; Agustina , Rizka Putri; Sumiyati; Pambudi, Nanda Dwi (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
The COVID-19 pandemic struck Indonesia, crippling various sectors of society. Signs of recovery from this downturn are starting to be felt in various regions across the country. With a spirit of collective recovery, IT Telkom Purworejo and its team aim to provide training and assistance related to technology. The theme chosen for the community service activity is "Internet for Villages." Desa Bleber has already established a close relationship as an adopted village of IT Telkom Purworejo. This community service activity aims to help improve internet infrastructure and provide socialization. The activity began with initiating a collaboration with Desa Bleber, surveying the village's internet conditions, and then continuing with socialization activities. Desa Bleber is located quite far from the city center of Purworejo, precisely on the Purworejo-Magelang border. This geographical location limits internet access. Desa Bleber only has one cellular transmitter. Based on the survey conducted with 15 residents at the village hall of Bleber, Kecamatan Bener, it was found that the arrangement of WiFi networks and the devices used for daily activities were still inadequate.This activity is expected to help improve infrastructure and provide technological insights to the community, thereby improving the living standards of the village residents. The survey results indicated that 85% of the participants use data quotas for internet access, 55% use the internet for less than 8 hours a day, 10% use the internet for business purposes, 85% consider the internet very important, 64% believe that internet speed needs to be increased, and 91% expressed satisfaction with the socialization activities.